2008
DOI: 10.2139/ssrn.1274732
|View full text |Cite
|
Sign up to set email alerts
|

The WTO Secretariat and the Role of Economics in DSU Panels and Arbitrations

Abstract: The WTO faces an increasing burden of arbitrating trade disputes between WTO member states. The disputes are economically complex and often lead to rulings that require changes in Members' economic policies. This paper provides a positive and normative analysis of a previously unaddressed question: What roles do economic analysis and economists play in WTO adjudication under the Dispute Settlement Understanding (DSU)? We identify a number of problems with the current Secretariat provision of technical economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The AB would have also benefitted by embracing economics in the matter of zeroing. Zeroing has been the single-most litigated issue at the AB despite the fact that the AB has repeatedly found that the practice violates the WTO Antidumping Agreement (ADA) [4]. The Panel's and AB's long and tortured history with zeroing is at least partly due to poorly constructed reasoning in early cases -logic that would have been more clear with a deeper user of economic analysis.…”
mentioning
confidence: 99%
“…The AB would have also benefitted by embracing economics in the matter of zeroing. Zeroing has been the single-most litigated issue at the AB despite the fact that the AB has repeatedly found that the practice violates the WTO Antidumping Agreement (ADA) [4]. The Panel's and AB's long and tortured history with zeroing is at least partly due to poorly constructed reasoning in early cases -logic that would have been more clear with a deeper user of economic analysis.…”
mentioning
confidence: 99%